Georgia : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2018)
The Government's decision to strengthen the infrastructure governance through improving the public investment management (PIM) and the public-private partnerships (PPPs) frameworks, is both timely and important. The government has an ambitious public investment agenda, to be implemented both through traditional public investment and with the help of private investors in the form of PPPs. Given the need to preserve fiscal sustainability in a context of limited fiscal space, avoiding inefficiencies and managing fiscal costs and risks arising from infrastructure projects will be crucial for advancing the government's public investment agenda. The authorities are working on a broad range of public financial management reforms, including improving the PIM framework and the legal and regulatory framework for PPPs and PPAs. Over the last decade, public investment in Georgia has been similar to the average of emerging market economies (EMEs). Since the mid-2000s, public investment accounted, on average, for one third of total investment. Public investment remained volatile, reaching a peak of 8.6 percent of GDP in 2007, declining in the aftermath of large global and regional shocks, and stabilizing at about 5.5 percent of GDP in recent years.